Hepatic hydatid disease. Experience of the last 13 years in Florida - González, Daniel; Vega, Alvaro; Monti, José; Torres, Marcos (Cirugía del Uruguay, 1999)
An analysis is made of the 13 year experience echinococcosis in the city of Florida. 131 patients were operated during that period, with a total of 151 hepatic hydatic cysts